La lucha por la hegemonía francesa en la medicina mexicana: el caso de los medicamentos para combatir la sífilis - Rosalina Estrada Urroz (Nuevo mundo - Mundos Nuevos, 2006)
Before the arrival of the penicillin, the discussions concerning the treatment of syphilis are express in the control and the regulation of prostitution and in the effectiveness of the drugs to treat the suffering. In this context, it is understandable that the arrival of the new chemist, named Salvarsan or 606, which has the same function of mercury and may substitute it, causes a commotion. Nevertheless there exist multiple reasons that explain the reticence and doubts of the efficiency of the new remedy, among them: the German origin of Salvarsan, the lack of experimentation of the drug in the country and the long presence of mercury as a curative, which would be attributed to French medicine.